Factors impacting on technical success in stroke thrombectomy: experience of a UK neuro-interventional unit. Issue 5 (May 2019) - Wareham, J.; Goswami, A.; Renowden, S.; Martinovic, O.; Shatti, D.; Phan, K.; Crossley, R.; Mortimer, A.
Abstract : AIM: To investigate factors that could impact on recanalisation and reperfusion in patients undergoing mechanical thrombectomy and to assess the technical success over time. MATERIALS AND METHODS: Two hundred consecutive patients who underwent thrombectomy for a proximal anterior circulation occlusion were dichotomised into equal groups (groups 1 and 2) based on the date that immediate access to emergency general anaesthesia (GA) commenced. RESULTS: Recanalisation success using thrombolysis in cerebral infarction (TICI) 2b/3 or TICI 2c/3 significantly improved in group 2 (67% versus 93%, p< 0.0001; 52% versus 78%, p= 0.0002). Symptomatic haemorrhage also reduced from 9% to 4%. Despite similar presentation Alberta Stroke Program Early (computed tomography) CT Scores (ASPECTS), post-procedural ASPECTS was significantly increased in group 2 (7; [interquartile range IQR 4–9] versus 8 [IQR 7–9]; p= 0.0034). The number of patients with a post procedural ASPECTS of 8–10 increased (46% versus 64%, p= 0.0155) and the difference in ASPECTS between pre- and post-thrombectomy CT was significantly lower (2 [IQR 1–4] versus 1 [IQR 0–2], p< 0.0001). GA use increased from 8% to 56% ( p= 0.0001) as did use of distal aspiration (59% versus 87%, p= 0.0001) mostly in combination with a stent-retriever. Failed access fell from 8% to 3%. When GA was used, successful recanalisation (TICI 2b/3) was achieved more frequently (90.5% versus 76.7%; OR 3.04, 1.2–7.69, p= 0.0187). CONCLUSION: Technical results for thrombectomy are improving over time. Technique modification, operator experience, and judicious use of GA may be contributing. Highlights: Technical outcomes for stroke thrombectomy are improving over time. Rates of recanalisation and timely reperfusion have increased. Final infarct extent has decreased. Procedural time, rates of failed access and symptomatic haemorrhage have decreased. Several factors could explain this, but general anaesthesia may facilitate difficult procedures. Case frequency has risen therefore operator experience is increasing.